n → ∞ lim ( 3 n 2 − n 3 + n ) = b a
The equation above holds true for positive coprime integers a and b . Find a + b .
Post your innovative solutions.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution Megh. But you forget to take brackets in 2nd step correct it.
l i m n → ∞ ( n 2 − n 3 ) 3 1 + n
Now take − n 3 common from root
− n ( 1 − n 1 ) 3 1 + n
Now as n → ∞
n 1 → 0
Binomial says
( 1 + x ) n = 1 + n x (when x <<< 1)
n → ∞ lim − n ( 1 − 3 n 1 ) + n = − n + 3 1 + n = 3 1
Good solution Really nice
L = n → ∞ lim ( 3 n 2 − n 3 + n ) = n → ∞ lim n ( 3 n 1 − 1 + 1 ) = n → ∞ lim n ( 1 − 3 1 − n 1 ) = n → ∞ lim n ( 1 − ( 1 − 3 n 1 − 9 n 2 1 − 8 1 n 3 5 − ⋯ ) ) = n → ∞ lim ( 3 1 + 9 n 1 + 8 1 n 2 5 + ⋯ ) = 3 1 By Taylor’s series expansion
Therefore, a + b = 1 + 3 = 4 .
L = n → ∞ lim 3 n 2 − n 3 + n = n → ∞ lim n 3 n 1 − 1 + n = n → ∞ lim n ( 3 n 1 − 1 + 1 ) = n → ∞ lim n 1 3 n 1 − 1 + 1 = n → ∞ lim 3 1 ⋅ ( n 1 − 1 ) − 2 / 3 = 3 1 0 0 case so apply L’Hopital’s Rule
In getting the closest value (though not exactly), I let infinity be equal to 999999.. Upon substituting, I got the answer 0.333... which is equal to 1/3.. hence, 1+3=4..
Problem Loading...
Note Loading...
Set Loading...
n ( 3 n 1 − 1 + n )
= n ( ( n 1 − 1 ) 3 1 + 1 3 1 )
now a + b = a 2 − a b + b 2 a 2 + b 3
thus
n ( ( n 1 − 1 ) 3 2 − ( n 1 − 1 ) 3 1 + 1 ( n 1 − 1 ) + 1 ) = 3 1